Effects of a Web-Based Intervention for PE Teachers on Students' Perceptions of Teacher Behaviors, Psychological Needs, and Intrinsic Motivation. Issue 3 (June 2019) - Tilga, Henri; Hein, Vello; Koka, Andre
Interventions based on self-determination theory to help teachers support their students' autonomy have measured teachers' autonomy-supportive and controlling behaviors as unidimensional constructs. This study investigated whether a Web-Based Autonomy-Supportive Intervention Program (WB-ASIP) for physical education (PE) teachers would alter their students' perceptions of (a) the teachers' multidimensional autonomy-supportive and controlling behaviors, (b) their own psychological need satisfaction and frustration, and (c) perceived intrinsic motivation. We found that WB-ASIP significantly increased students' perceptions of all autonomy-supportive teacher behaviors and students' need satisfaction. At follow-up, we found that WB-ASIP led to a significant decrease in students' perception of teacher intimidation behaviors and students' autonomy frustration. These results suggest that a web-based intervention program to enhance PE teachers' autonomy-supportive behavior and minimize their controlling behavior was partially effective in positively changing their students' perceptions.